Semiconductors as sensitisers for the radical addition of tertiary amines to electron deficient alkenes - Siniša Marinković; Norbert Hoffmann (International Journal of Photoenergy)
Using heterogeneous photocatalysis, the radical addition of tertiary amines with electron deficient alkenes can be performed in high yields (up to 98%) and high facial diastereoselectivity. The photochemical induced electron transfer process initiates the radical chain reaction and inorganic semiconductors like TiO2 and ZnS were used. According to the proposed mechanism, the reaction takes place at the surface of the semiconductor and the termination step results from an interfacial electron transfer from the conduction band to the oxoallyl radical intermediate. Frequently, semiconductors are used for the mineralisation of organic compounds in wastewater. However, in this case, they are used in organic synthesis. The process can be performed in a convenient way and is particularly interesting from the ecological and economical point of view. No previous functionalization of the tertiary amines is necessary for C − C bond formation. Further on, the amines are used both as reactant and as solvent. The excess is recycled by distillation and the inexpensive sensitiser can be easily removed by filtration. In this way, products of high interest for organic synthesis are obtained by a diastereoselective radical reaction.